SSCS Model Based E-Worksheet: Needs Analysis to Stimulate Critical Thinking Skills - Ahmad Saroji; Undang Rosidin; Chandra Ertikanto; Kartini Herlina; Munadhirotul Azizah (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the need to develop an e-Worksheet based on the SSCS model to stimulate critical thinking skills. This study uses a qualitative descriptive method to provide an overview of the implementation of critical thinking skills in high school during learning that implements the independent curriculum. This research was conducted in March 2023. The data source was obtained using the non-test technique in the form of an open questionnaire. The subjects in this study were 15 physics teachers spread across 3 provinces in Indonesia, including Lampung, Central Java and South Sumatra. The data analysis technique is the Miles & Huberman (2018) analysis technique which is carried out continuously until the data is saturated. Data analysis involves three steps, data reduction, data presentation, and verification. The results of the study show that critical thinking skills have not been fully implemented in physics learning in senior high schools in the independent curriculum. Therefore, the development of an e-Worksheet based on the SSCS model is needed to stimulate students' critical thinking skills.